Comparison of Ethanolic and Aqueous Populus balsamifera L. Bud Extracts by Different Extraction Methods: Chemical Composition, Antioxidant and Antibacterial Activities - Monika Stanciauskaite; Mindaugas Marksa; Lina Babickaite; Daiva Majiene; Kristina Ramanauskiene (MDPI AG, 2021)
The balsam poplar (Populus balsamifera L.) buds that grow in Lithuania are a polyphenol-rich plant material with a chemical composition close to that of propolis. In order to potentially adapt the extracts of this plant's raw material for therapeutic purposes, it is important to carry out detailed studies on the chemical composition and biological activity of balsam poplar buds. An important step is to evaluate the yield of polyphenols by different extraction methods and using different solvents. According to our research, extracts of balsam poplar buds collected in Lithuania are dominated by p-coumaric (496.9-13,291.2 µg/g), cinnamic acid (32.9-11,788.5 µg/g), pinobanksin (34.9-1775.5 µg/g) and salicin (215.3-1190.7 µg/g). The antioxidant activity of poplar buds was evaluated by the ABTS (2,2-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), DPPH (2,2-diphenyl-1-picrylhydrazyl) and FRAP (ferric-reducing antioxidant power) methods, all extracts showed antioxidant activity and the obtained results correlated with the obtained amounts of total phenolic compounds in the extracts (ABTS r = 0.974; DPPH r = 0.986; FRAP r = 0.955, p < 0.01). Studies of antimicrobial activity have shown that ethanolic extracts have an antimicrobal activity effect against Staphylococcus aureus, Enterococcus faecalis and Escherichia coli. The extracts showed a better antimicrobal activity against gram-positive bacteria.